Analysis of the Task Technology Fit Suitability of the SiNonA Application and its Impact on Improving the Performance of Non-ASN Employees - Melinda Kurnia Putri; Nining Ariati; Dhamayanti Dhamayanti (JEECS (Journal of Electrical Engineering and Computer Sciences), 2026)
The implementation of the Electronic-Based Government System (SPBE) encourages government institutions to utilize information technology to improve employee effectiveness and administrative efficiency. One implementation in Ogan Ilir Regency is the SiNonA application, which is used as a digital attendance system for Non-ASN employees. However, several problems are still encountered in its implementation, such as limited application features, difficulties in system usage, and the mismatch between system capabilities and employee work requirements. Previous studies on digital attendance systems mostly focused on usability, system quality, and technology acceptance, while studies examining the suitability between technology characteristics and employee task requirements using the Task Technology Fit (TTF) approach are still limited, especially in the government sector for Non-ASN employees. Therefore, this study aims to analyze the influence of Task Characteristics and Technology Characteristics on Task Technology Fit and its impact on employee performance improvement in using the SiNonA application. This study used a quantitative approach with a survey method involving 353 respondents selected using the Slovin formula. Data were collected through Likert-scale questionnaires and analyzed using the PLS-SEM method with SmartPLS software. The results showed that Task Characteristics and Technology Characteristics had a positive and significant effect on Task Technology Fit, while Task Technology Fit also had a positive and significant effect on employee performance improvement. These findings indicate that the suitability between technology and work tasks plays an important role in improving the effectiveness, efficiency, and productivity of Non-ASN employees in using the SiNonA application.